Visible to NIR down-shifting and NIR to visible upconversion luminescence in Ca14Zn6Ga10O35:Mn4+, Ln3+ (Ln=Nd, Yb, Er). (February 2019) - Lv, Yang; Jin, Yahong; Sun, Tong; Su, Jinglan; Wang, Chuanlong; Ju, Guifang; Chen, Li; Hu, Yihua
Abstract: A series of phosphors Ca14 Zn6 Ga10 O35 :Mn 4+, Ln 3+ (Ln = Nd, Yb, Er) have been prepared by conventional high temperature solid-state reaction. Mn 4+ single doped Ca14 Zn6 Ga10 O35 shows deep red emitting, and it can obtain NIR emission when co-doped with Ln 3+ in Ca14 Zn6 Ga10 O35 :Mn 4+ via an efficient energy transfer from Mn 4+ to Ln 3+ . This process mainly is attributed to the dipole-dipole interaction mechanism. Visible-NIR to NIR down-shifting is realized via the energy transfer from Mn 4+ to Ln 3+ ions. Reversely, the green emission of Er 3+ can be observed upon 980 nm light excitation, and the red emitting of Mn 4+ appears in Mn 4+ and Er 3+ co-doped Ca14 Zn6 Ga10 O35 phosphors through the up-converted energy transfer from Er 3+ to Mn 4+ . Two-photon processes are required to populate the 2 H11/2, 4 S3/2 and 4 F9/2 excited states of Er 3+ . The dual-mode luminescence mechanism, including energy transfer from Mn 4+ to Ln 3+ and up-conversion energy transfer from Er 3+ to Mn 4+, has been discussed in detail. Graphical abstract: Highlights: Mn 4+ single doped Ca14 Zn6 Ga10 O35 shows deep red emitting. The NIR luminescence is observed by Ln 3+ (Ln = Nd, Er, Yb) ions co-doping in Ca14 Zn6 Ga10 O35 :Mn 4+ . Up-conversion green emission of Er 3+ and red emission of Mn 4+ have obtained upon 980 nm light exaction.